Maternidade e (des)proteção social: quando a questão da mulher se torna visível - Dantas, Hílkia Maria De Carvalho (2022)
The woman/mother of the working class that lives from the (de) protective work situation and the evaluations through which she is put when the matter is the wellbeing of her children, is key in this dissertation. This research intends to comprehend how much the Brazilian historical process - which is based in slavery of black people and colonialism, with strong conservative and authoritarian bias, that establishes inequalities of class, ethnicity, race and social sex relations - maintain to this day it’s historical ties and influence over the professional duty, contributing to biased judgements over the way of living and the protective role of the woman, favoring judicialization of their lives and diminishing their rights. The theoretical reference established by the bibliographic research composes with the qualitative methodology, through interviews with two maternity hospital professionals, one worker of the justice system and one substance user. A quantitative research was also made, gathering data from the São Paulo city and the maternity hospital territory, the profile of the women who had their cases forwarded to the tutelary council and/or to the childhood and youth court, the social service interventions and requisitions were also gathered, to establish a link between these women reality and the professional work, in order to widen this matter’s discussion and to contribute to analysis of public policies, in the scope of the sanitary revision. Was also intended to apprehend if the services and the society still maintain the false dichotomy between the youth rights and those of their mothers and families, presenting interpretations in the sense of how much the capitalist system puts these rights in conflict, generating a continuity to the prejudice and stigmas directed to the poor. The results are presented in four chapters, the fist shows how much the country’s historical process favors the Brazilian people devaluation and it’s repercussions to women; the second chapter brings the perspective between inequalities of class, ethnicity, race and social sex relations, to try to comprehend the women role in the Brazilian society; the third chapter clashes the professional work in health and the dispute between the sanitary revision project and the privatizing project, that influences the professional posture, the articulations between the teams and the care net. The fourth and last chapter presents the work process, continuities, ruptures, progresses and challenges related to the judicialization linked to maternity